Implementación de una planta de acción para mejorar el clima laboral y el desempeño del personal en la empresa CAFU :sistematización de la experiencia - Sanafria Jiménez, Carla Gabriela (2017)
The present project is aimed at verifying the influence that the working climate has on the performance of CAFU's employees. The inadequate performance of the employees of the company has pushed for the completion of the project and demonstrate that a bad working environment can influence the performance of employees and their job satisfaction, for which two types of measurement tools will be used: Performance assessment, which will help us identify information relevant to the project, detecting behaviors, skills and competencies with more deficits. The second tool that will be used in the project will be the preparation of a labor climate survey, which will give us information about the welfare of the employee in his job, how he feels in the social field, with his colleagues, Its commitment, a sense of belonging to the company, conditions of the job, focusing on the ergonomic field, how satisfied the employee is with the recognition and benefits he receives from the company, this collection of real data will help us Define the hypothesis. The intervention project will help us to define the influence of the work climate on the performance of the employees, which can affect a bad working environment in the productivity, efficiency and motivation of a collaborator when he / she is in the job, with The objective of proposing strategies and action plans to achieve an improvement in the performance of the collaborators covering all the factors of measurement of the labor atmosphere and later of performance evaluation, in the same way to create a structure of feedback of the performance evaluation to use it Not only every six months, but also to evaluate the probation period of 90 days, given the company's need to select the human capital competent and committed to its job and to the company.